From Mortal Sins to Individual Pride: Transformations of Sexually Motivated Crimes in the Czech Lands from the Middle Ages to the Present - Martin Slaboch; Petr Kokaisl (Genealogy)
The legal and social perception of sexually motivated crimes has undergone profound transformations in the Czech lands from the Middle Ages to the present. Acts once considered grave moral transgressions, punishable by death, have been gradually decriminalised or even integrated into the realm of personal identity and cultural self-expression. This article examines the evolving legal frameworks and societal attitudes towards such offences, with a particular focus on their implications for family structures, inheritance rights, and genealogical continuity. By analysing historical judicial records—primarily early modern pitch books—alongside contemporary legislation, we highlight the shifting boundaries between crime, morality, and individual rights. Methodologically, this study combines a historical–legal analysis with comparative criminology to elucidate the changing regulatory mechanisms governing sexual behaviour. The findings illustrate that, while legal norms have progressively moved away from religious morality toward individual freedoms, some taboos persist, reflecting enduring social anxieties. The Czech case serves as a model for broader European trends, offering valuable insights into the interplay between law, social norms, and genealogical structures across different historical periods.